Sengketa Tiada Putus: Matriarkat, Reformisme Agama, dan Kolonialisasi di Minangkabau - Hadler, Jeffrey - (TINGKAP, 2013)
This article provides a rich social history of the Minangkabau of West Sumatra by tracing the patterns of continuity and change that have characterized modern Minangkabau history, stretching from the end of the Padri rebellion into the twilight years of Dutch colonial rule in West Sumatra. His primary interest, however, lies largely in broader social changes, in education, gender relations and home life for the Minangkabau. With great nuance and depth, Hadler shows how the Minangkabau â€œmatriarchateâ€ responded creatively to change and to the forces of capitalism and modernity by questioning elemental cultural definitions and, as a result, producing some of the countryâ€™s leading nationalist intellectuals and activists. Kata Kunci: Matriarkat, reformisme agama, kolonialisasi